The weather today rocks or sucks for my tree: exploring the understanding of climate impacts on forests at high school level through tweets - Mölg, Thomas; Schubert, Jan Christoph; Debel, Annette; Höhnle, Steffen; Steppe, Kathy; Wehrmann, Sibille; Bräuning, Achim (Geoscience Communication, 2024)
With the progression of global warming, impacts on the human sphere will undoubtedly increase. One promi- nent example at mid-latitudes is the stress on forests caused by climate change, which the BayTreeNet project (https: //baytreenet.de/, last access: 30 July 2024) addresses from an interdisciplinary viewpoint. Scientists from physical clima- tology, dendroecology, and educational research collaborate to examine how longterm changes in weather patterns affect the state of trees, and how the atmosphere–tree relation can be used to the advantage of improving the communication of climate change effects to, in particular, high school students. This article presents a 1-week case study for the sum- mer of 2021, when a distinct variability in weather patterns induced significant tree responses. The students of seven selected partner schools commented on the measured tree and weather data, which were available in real time, in the form of tweets and in conjunction with their educational geography program. The analyses of the tweets reveal that the stu- dents succeed in verbalizing the measured weather and, furthermore, manage to draw links between the stem diameter changes in trees and the weather variability. Problems arise with the use of less perceivable variables like the sap flow in the trees; also, the student posts exhibit shortcomings in establishing causal connections. Hence, the case study points to a discrepancy between describing basic environmental in- formation and appreciating or understanding the underlying mechanistic links. This point will serve to refine future classroom concepts and, moreover, to enhance the communication of climate change effects on forests to the general public.
Keywords: Climate Change; Geography Education; Research